Aluminum alloy profile for new energy automobile

By optimizing the element composition and process flow of aluminum alloy materials, adding rare earth metal elements La, Pr and Gd, and performing refining, homogenizing and surface anti-corrosion treatment, the problem of insufficient mechanical properties and corrosion resistance of aluminum alloy materials is solved, and the problem of insufficient mechanical properties and corrosion resistance of aluminum alloy materials is achieved. It has significantly improved mechanical properties and corrosion resistance, and meets the high-strength and high corrosion resistance requirements of new energy vehicles.

CN119265459AActive Publication Date: 2025-01-07LINYI UNIVERSITY +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411375939.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing aluminum alloy materials have insufficient mechanical properties and corrosion resistance, making it difficult to meet the high-strength and high corrosion resistance requirements in the field of new energy vehicles.

Method used

By optimizing the element composition, rare earth metal elements La, Pr and Gd are added, and refining, homogenizing, forming and surface anti-corrosion treatment processes are adopted to improve the mechanical properties and corrosion resistance of aluminum alloy profiles.

Benefits of technology

The mechanical properties of aluminum alloy profiles have been improved, the tensile strength and yield strength have reached more than 320MPa, and the corrosion resistance has been significantly enhanced, which is suitable for the use needs of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265459A_ABST
    Figure CN119265459A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy profile for a new energy automobile, and belongs to the technical field of new energy materials. The aluminum alloy profile comprises the following components in percentage by mass: 0.14%-0.19% of Fe, 0.58%-0.66% of Si, 0.6%-1.3% of Mg, 0.25%-0.35% of Cu, 0.07%-0.15% of Mn, 0.14%-0.22% of Cr, 0.01%-0.05% of Zn, 0.03%-0.15% of Ti, 0.6%-0.9% of composite rare earth metal elements and the balance of Al and impurities, and the total content of the impurities is not greater than 0.25%. According to the method, the aluminum alloy profile is optimized from the two aspects of element composition and surface treatment, rare earth metal elements La, Pr and Gd with different atomic radiuses and qualitative change capacities are added, grains of the aluminum alloy are effectively refined, a surface treating agent is sprayed subsequently, and the mechanical property and corrosion resistance of the aluminum alloy profile are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to an aluminum alloy profile for new energy vehicles. Background Art

[0002] With the development of automobile technology and the improvement of people's environmental awareness, the pollution caused by exhaust gas of traditional fuel vehicles has received great attention from countries around the world. In recent years, new energy vehicles have entered the "fast track" and have been recognized by more and more consumers. Compared with traditional fuel vehicles, the weight of the fuel cell group in new energy vehicles (taking electric vehicles as an example) is as high as hundreds of kilograms, which puts forward higher requirements for the lightweight of new energy vehicles.

[0003] Using lightweight materials to replace traditional ordinary sheet metal materials and reduce the weight of the vehicle body is one of the mainstream solutions to increase vehicle range. Materials suitable for lightweighting of automobiles generally include aluminum alloys, magnesium alloys, high-strength steel and composite materials. The earth's aluminum ore resources are abundant and are an important non-ferrous metal. Aluminum alloy materials produced by adding other elements to pure aluminum materials take into account the needs of cost, performance and lightweight effects, and are one of the popular application directions of lightweight component materials.

[0004] Existing aluminum alloy profiles have one or more properties such as tensile strength, yield strength and corrosion resistance that are insufficient, making it difficult to meet the actual use requirements of electric vehicles and various parts and components. Chinese patent application CN201811558425.9 discloses a high-strength aluminum alloy profile for a battery tray of a new energy vehicle and a preparation method thereof. By improving the ingredients and adopting a gradient heating process, the temperature of the aluminum rod heated before extrusion is gradually reduced from front to back along its axis to form a temperature gradient and realize isothermal extrusion, so that the core surface temperature of the product after heating and processing is uniform, the surface color is bright, and the mechanical property deviation is small. The aluminum alloy profile obtained by this preparation method has a tensile strength of more than 310MPa and a yield strength of 270MPa, which improves the product quality and thus improves the overall quality of new energy vehicles.

[0005] However, the mechanical properties of current aluminum alloy materials cannot meet the latest high-strength and high-corrosion resistance requirements in the current new energy vehicle field. How to develop an aluminum alloy profile with excellent comprehensive performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The present invention aims to solve the problems existing in the prior art by optimizing the element composition and spraying corrosion inhibitors, thereby greatly improving the mechanical properties and corrosion resistance of aluminum alloy materials. The present invention is suitable for use in various parts of new energy vehicles and has broad application prospects.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] An aluminum alloy profile for new energy vehicles includes the following components by mass percentage: Fe 0.14-0.19%, Si 0.58-0.66%, Mg 0.6-1.3%, Cu 0.25-0.35%, Mn 0.07-0.15%, Cr 0.14-0.22%, Zn 0.01-0.05%, Ti 0.03-0.15%, composite rare earth metal elements 0.6-0.9%, and the balance is Al and impurities, wherein the total impurity content is not more than 0.25%.

[0009] Furthermore, the composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:1.

[0010] A method for preparing an aluminum alloy profile for new energy vehicles comprises the following preparation steps:

[0011] (1) Melting: Prepare the raw materials of various metal elements in proportion, melt the aluminum ingot, add other metal elements, heat and melt, and stir evenly to obtain an alloy melt;

[0012] (2) Refining treatment: refining the alloy melt obtained in step (1) to complete degassing and impurity removal;

[0013] (3) Casting: Casting the refined melt into an aluminum alloy ingot at a casting temperature of 700-750°C and a casting speed of 30-50 mm / min;

[0014] (4) Homogenization treatment: placing the aluminum alloy ingot in a homogenization furnace for homogenization treatment at a temperature of 540-560° C. for a holding time of 5-10 h;

[0015] (5) Cooling treatment: cooling the homogenized aluminum alloy ingot to 150-180° C. at a cooling rate of 100-120° C. / hour, and then cooling to room temperature by water mist;

[0016] (6) Forming: The aluminum alloy ingot after cooling is sent into an extruder for extrusion molding, the extrusion temperature is 475-485°C, the extrusion rate is 10-12m / min, and the extrusion pressure is 120-150MPa;

[0017] (7) Quenching and cooling: Quench the extruded material to room temperature, the quenching temperature is 455-465°C, keep it warm for 3-4 hours, and then water cool it to room temperature;

[0018] (8) Artificial aging: The profiles after quenching and cooling are artificially aged at a temperature of 190-200°C for 5-7 hours, and finally cooled to room temperature;

[0019] (9) Surface anti-corrosion treatment: Spray the surface treatment agent on the profile surface, cure at 170°C for 30 minutes, and then cool naturally.

[0020] Furthermore, the smelting temperature in step (1) is 740-750° C. and the smelting time is 5-7 h.

[0021] Furthermore, the refining method in step (2) is: using argon gas to blow a refining agent into the aluminum liquid formed by smelting to perform furnace refining, the amount of the refining agent is 1.5-2.5% of the weight of the alloy melt, and the furnace refining time is 17-20 minutes.

[0022] Furthermore, the surface treatment agent in step (9) is a silica sol solution of a corrosion inhibitor, and the specific preparation method is as follows: 0.1mmol 2,5-furandicarboxylic acid and 0.1mmol cerium nitrate are added in sequence to 5ml of a mixed solvent, wherein the mixed solvent consists of N,N-dimethylacetamide, ethanol and deionized water in a volume ratio of 1:1:1; the mixed solution is ultrasonically treated for 15min and then transferred to a reactor, reacted at 95°C for 48h, cooled to room temperature and dried to obtain a corrosion inhibitor; nano-silica sol is taken, 1-3% of the corrosion inhibitor by mass of the nano-silica sol is added under ultrasound, after being fully dispersed, the pH of the system is adjusted to 4.5-5.5, and 10-15% of the mass of the nano-silica sol is added with methyltrimethoxysilane, and the mixture is mixed and reacted at room temperature for 8h to obtain a surface treatment agent.

[0023] Furthermore, the nano-silica sol has an average particle size of 30-50 nm and a mass concentration of 20-50%.

[0024] Furthermore, the surface treatment agent is sprayed with a thickness of 1-3 μm.

[0025] Beneficial effects:

[0026] (1) The present invention optimizes aluminum alloy profiles from two perspectives: element composition and surface treatment, in order to improve the mechanical properties and corrosion resistance of aluminum alloy profiles. On the one hand, the present invention adds rare earth metal elements La, Pr and Gd with different atomic radii and metamorphic abilities. After the three are mixed in equal proportions, they show obvious synergistic effects, effectively refine the grains of the aluminum alloy, and the refined grains are distributed evenly and dispersed in the aluminum matrix, playing a role of dispersion strengthening and fine grain strengthening, thereby effectively improving the strength of the material. At the same time, the rare earth metal elements La, Pr and Gd have strong degassing and impurity removal effects, helping to remove harmful impurities in aluminum and aluminum alloys, such as hydrogen, oxygen and sulfur, and further refine the grains or change their morphology. At the same time, the refined microstructure can effectively hinder crack propagation and grain boundary sliding during the corrosion process, and improve the corrosion resistance of the material.

[0027] (2) Secondly, the refining treatment and homogenization treatment of the present invention can further effectively remove hydrogen and various harmful impurities, prevent the formation of pores and slag inclusions during casting, and improve the mechanical properties of aluminum alloy profiles. Homogenization treatment can effectively reduce and eliminate intracrystalline segregation, improve the surface quality of the finished aluminum alloy profile, and the surface of the finished profile is smooth without obvious stripes and particles. And after the homogenization treatment, a rapid cooling treatment is set to make the precipitate dispersed in a fine shape, which is beneficial to refine the grains and improve the tensile strength and yield strength of the finished aluminum alloy profile.

[0028] (3) For the surface anticorrosion treatment of the formed profile, the present invention uses dipentafurandicarboxylic acid as an organic ligand and Ce ions as metal cation centers, adopts a solvent thermal method to prepare a corrosion inhibitor, and disperses it in a mixture of methyltrimethoxysilane as a monomer and nano-SiO 2 The modified silica sol prepared by sol copolymerization is then sprayed on the surface of the aluminum alloy, which has good adhesion to the aluminum alloy matrix and can continuously and effectively play an anti-corrosion and corrosion-resistant role. At the same time, the presence of nano-silicon dioxide particles can effectively fill the tiny pores on the surface of the aluminum alloy, improve the surface smoothness of the material, and significantly improve the strength of the coating, and the wear resistance of the aluminum alloy surface is improved. The obtained aluminum alloy profile has excellent mechanical properties and strong corrosion resistance, and is particularly suitable for use in parts with anti-corrosion requirements such as new energy vehicle motor batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The grain morphology diagrams of the obtained profiles of the embodiments and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0031] Example 1

[0032] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0033] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:1.

[0034] A method for preparing an aluminum alloy profile for new energy vehicles comprises the following preparation steps:

[0035] (1) Melting: Prepare the raw materials of various metal elements in proportion, melt the aluminum ingot, add other metal elements, heat and melt, and stir evenly to obtain an alloy melt;

[0036] (2) Refining treatment: refining the alloy melt obtained in step (1) to complete degassing and impurity removal;

[0037] (3) Casting: Casting the refined melt into an aluminum alloy ingot at a casting temperature of 700-750°C and a casting speed of 30 mm / min;

[0038] (4) Homogenization treatment: The aluminum alloy ingot is placed in a homogenization furnace for homogenization treatment at a temperature of 540-560°C for a holding time of 5 hours;

[0039] (5) Cooling treatment: cooling the homogenized aluminum alloy ingot to 150-180° C. at a cooling rate of 100-120° C. / hour, and then cooling to room temperature by water mist;

[0040] (6) Forming: The aluminum alloy ingot after cooling is sent into an extruder for extrusion molding at an extrusion temperature of 475-485°C, an extrusion rate of 10 m / min, and an extrusion pressure of 120 MPa;

[0041] (7) Quenching and cooling: Quench the extruded material to room temperature, the quenching temperature is 455-465°C, keep it warm for 3 hours, and then water cool it to room temperature;

[0042] (8) Artificial aging: The profiles after quenching and cooling are artificially aged at a temperature of 190-200°C for 5 hours and finally cooled to room temperature;

[0043] (9) Surface anti-corrosion treatment: Spray the surface treatment agent on the profile surface, cure at 170°C for 30 minutes, and then cool naturally.

[0044] The smelting temperature of step (1) is 740-750° C. and the smelting time is 5 h.

[0045] The refining method in step (2) is: using argon gas to blow a refining agent into the aluminum liquid formed by smelting to carry out furnace refining, the amount of the refining agent used is 1.5% of the weight of the alloy melt, and the furnace refining time is 17 minutes.

[0046] Step (9) The surface treatment agent is a silica sol solution of a corrosion inhibitor, and the specific preparation method is as follows: 0.1mmol 2,5-furandicarboxylic acid and 0.1mmol cerium nitrate are added in sequence to 5ml of a mixed solvent, wherein the mixed solvent consists of N,N-dimethylacetamide, ethanol and deionized water in a volume ratio of 1:1:1; the mixed solution is ultrasonically treated for 15min and then transferred to a reactor, reacted at 95°C for 48h, cooled to room temperature and dried to obtain a corrosion inhibitor; nano-silica sol is taken, 1-3% of the corrosion inhibitor by mass of the nano-silica sol is added under ultrasound, after being fully dispersed, the pH of the system is adjusted to 4.5-5.5, and 10% of the mass of the nano-silica sol is added with methyltrimethoxysilane, and the mixture is mixed and reacted at room temperature for 8h to obtain a surface treatment agent.

[0047] The nano silica sol has an average particle size of 30-50 nm and a mass concentration of 20%.

[0048] The surface treatment agent spraying thickness is 1-3μm.

[0049] Example 2

[0050] An aluminum alloy profile for new energy vehicles includes the following components, calculated by mass percentage: 0.16% Fe, 0.62% Si, 1% Mg, 0.3% Cu, 0.1% Mn, 0.2% Cr, 0.03% Zn, 0.1% Ti, 0.75% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0051] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:1.

[0052] A method for preparing an aluminum alloy profile for new energy vehicles comprises the following preparation steps:

[0053] (1) Melting: Prepare the raw materials of various metal elements in proportion, melt the aluminum ingot, add other metal elements, heat and melt, and stir evenly to obtain an alloy melt;

[0054] (2) Refining treatment: refining the alloy melt obtained in step (1) to complete degassing and impurity removal;

[0055] (3) Casting: Casting the refined melt into an aluminum alloy ingot at a casting temperature of 700-750°C and a casting speed of 40 mm / min;

[0056] (4) Homogenization treatment: The aluminum alloy ingot is placed in a homogenization furnace for homogenization treatment at a temperature of 540-560°C for 8 hours;

[0057] (5) Cooling treatment: cooling the homogenized aluminum alloy ingot to 150-180° C. at a cooling rate of 100-120° C. / hour, and then cooling to room temperature by water mist;

[0058] (6) Forming: The aluminum alloy ingot after cooling is sent into an extruder for extrusion molding at an extrusion temperature of 475-485°C, an extrusion rate of 12 m / min, and an extrusion pressure of 130 MPa;

[0059] (7) Quenching and cooling: Quench the extruded material to room temperature, the quenching temperature is 455-465°C, keep it warm for 3 hours, and then water cool it to room temperature;

[0060] (8) Artificial aging: The profiles after quenching and cooling are artificially aged at a temperature of 190-200°C for 6 hours, and finally cooled to room temperature;

[0061] (9) Surface anti-corrosion treatment: Spray the surface treatment agent on the profile surface, cure at 170°C for 30 minutes, and then cool naturally.

[0062] The smelting temperature of step (1) is 740-750° C. and the smelting time is 6 hours.

[0063] The refining method in step (2) is: using argon gas to blow a refining agent into the aluminum liquid formed by smelting to carry out furnace refining, the amount of the refining agent is 2% of the weight of the alloy melt, and the furnace refining time is 20 minutes.

[0064] Step (9) The surface treatment agent is a silica sol solution of a corrosion inhibitor, and the specific preparation method is as follows: 0.1mmol 2,5-furandicarboxylic acid and 0.1mmol cerium nitrate are added in sequence to 5ml of a mixed solvent, wherein the mixed solvent consists of N,N-dimethylacetamide, ethanol and deionized water in a volume ratio of 1:1:1; the mixed solution is ultrasonically treated for 15min and then transferred to a reactor, reacted at 95°C for 48h, cooled to room temperature and dried to obtain a corrosion inhibitor; nano-silica sol is taken, 1-3% of the corrosion inhibitor by mass of the nano-silica sol is added under ultrasound, after being fully dispersed, the pH of the system is adjusted to 4.5-5.5, and 12% of the mass of the nano-silica sol is added with methyltrimethoxysilane, and the mixture is mixed and reacted at room temperature for 8h to obtain a surface treatment agent.

[0065] The nano silica sol has an average particle size of 30-50 nm and a mass concentration of 30%.

[0066] The surface treatment agent spraying thickness is 1-3μm.

[0067] Example 3

[0068] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.19% Fe, 0.66% Si, 1.3% Mg, 0.35% Cu, 0.15% Mn, 0.22% Cr, 0.05% Zn, 0.15% Ti, 0.9% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0069] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:1.

[0070] A method for preparing an aluminum alloy profile for new energy vehicles comprises the following preparation steps:

[0071] (1) Melting: Prepare the raw materials of various metal elements in proportion, melt the aluminum ingot, add other metal elements, heat and melt, and stir evenly to obtain an alloy melt;

[0072] (2) Refining treatment: refining the alloy melt obtained in step (1) to complete degassing and impurity removal;

[0073] (3) Casting: Casting the refined melt into an aluminum alloy ingot at a casting temperature of 700-750°C and a casting speed of 50 mm / min;

[0074] (4) Homogenization treatment: The aluminum alloy ingot is placed in a homogenization furnace for homogenization treatment at a temperature of 540-560°C for 10 hours;

[0075] (5) Cooling treatment: cooling the homogenized aluminum alloy ingot to 150-180° C. at a cooling rate of 100-120° C. / hour, and then cooling to room temperature by water mist;

[0076] (6) Forming: The aluminum alloy ingot after cooling is sent into an extruder for extrusion molding at an extrusion temperature of 475-485°C, an extrusion rate of 12 m / min, and an extrusion pressure of 150 MPa;

[0077] (7) Quenching and cooling: Quench the extruded material to room temperature, the quenching temperature is 455-465°C, keep it for 4 hours, and then water cool it to room temperature;

[0078] (8) Artificial aging: The profiles after quenching and cooling are artificially aged at a temperature of 190-200°C for 7 hours and finally cooled to room temperature;

[0079] (9) Surface anti-corrosion treatment: Spray the surface treatment agent on the profile surface, cure at 170°C for 30 minutes, and then cool naturally.

[0080] The smelting temperature of step (1) is 740-750° C. and the smelting time is 7 h.

[0081] The refining method in step (2) is: using argon gas to blow a refining agent into the aluminum liquid formed by smelting to carry out furnace refining, the amount of the refining agent is 2.5% of the weight of the alloy melt, and the furnace refining time is 20 minutes.

[0082] Step (9) The surface treatment agent is a silica sol solution of a corrosion inhibitor, and the specific preparation method is as follows: 0.1mmol 2,5-furandicarboxylic acid and 0.1mmol cerium nitrate are added in sequence to 5ml of a mixed solvent, wherein the mixed solvent consists of N,N-dimethylacetamide, ethanol and deionized water in a volume ratio of 1:1:1; the mixed solution is ultrasonically treated for 15min and then transferred to a reactor, reacted at 95°C for 48h, cooled to room temperature and dried to obtain a corrosion inhibitor; nano-silica sol is taken, 1-3% of the corrosion inhibitor by mass of the nano-silica sol is added under ultrasound, after being fully dispersed, the pH of the system is adjusted to 4.5-5.5, and 15% of the mass of the nano-silica sol is added with methyltrimethoxysilane, and the mixture is mixed and reacted at room temperature for 8h to obtain a surface treatment agent.

[0083] The nano silica sol has an average particle size of 30-50 nm and a mass concentration of 50%.

[0084] The surface treatment agent spraying thickness is 1-3μm.

[0085] Comparative Example 1

[0086] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% rare earth metal elements, and the balance being Al and impurities, wherein the total impurity content is not more than 0.25%.

[0087] The rare earth metal element is La.

[0088] Compared with Example 1, this comparative example is the same as Example 1 except that only La is used as the rare earth metal element. Other raw materials and preparation processes are the same as those of Example 1.

[0089] Comparative Example 2

[0090] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% rare earth metal elements, and the balance being Al and impurities, wherein the total impurity content is not more than 0.25%.

[0091] The rare earth metal element is Pr.

[0092] Compared with Example 1, this comparative example is the same as Example 1 except that only Pr is used as the rare earth metal element. Other raw materials and preparation processes are the same as those of Example 1.

[0093] Comparative Example 3

[0094] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% rare earth metal elements, and the balance being Al and impurities, wherein the total impurity content is not more than 0.25%.

[0095] The rare earth metal element is Gd.

[0096] Compared with Example 1, this comparative example is the same as Example 1 except that only Gd is used as the rare earth metal element. Other raw materials and preparation processes are the same as those of Example 1.

[0097] Comparative Example 4

[0098] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0099] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 2:1:1.

[0100] Compared with Example 1, this comparative example has the same raw materials and preparation process as Example 1 except that the mass ratio of the rare earth metal elements is different.

[0101] Comparative Example 5

[0102] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0103] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:2:1.

[0104] Compared with Example 1, this comparative example has the same raw materials and preparation process as Example 1 except that the mass ratio of the rare earth metal elements is different.

[0105] Comparative Example 6

[0106] An aluminum alloy profile for new energy vehicles includes the following components, measured by mass percentage: 0.14% Fe, 0.58% Si, 0.6% Mg, 0.25% Cu, 0.07% Mn, 0.14% Cr, 0.01% Zn, 0.03% Ti, 0.6% composite rare earth metal elements, and the remainder Al and impurities, wherein the total impurity content is not more than 0.25%.

[0107] The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:2.

[0108] Compared with Example 1, this comparative example has the same raw materials and preparation process as Example 1 except that the mass ratio of the rare earth metal elements is different.

[0109] Comparative Example 7

[0110] Compared with Example 1, this comparative example uses the same raw materials and preparation process as Example 1 except that the composition of the surface treatment agent is changed, that is, only the modified silica sol is used.

[0111] The surface treatment agent in step (9) is a silica sol solution, and the specific preparation method is: take nano silica sol, adjust the system pH to 4.5-5.5, add methyltrimethoxysilane at 10% of the mass of the nano silica sol, mix and react at room temperature for 8 hours to obtain the surface treatment agent.

[0112] The nano silica sol has an average particle size of 30-50 nm and a mass concentration of 20%.

[0113] Performance Testing

[0114] Test sample: Aluminum profiles were prepared according to the methods of Examples 1-3 and Comparative Examples 1-7;

[0115] Mechanical properties test: The mechanical properties of the aluminum profile samples provided in the embodiments and comparative examples were tested according to the testing standard of GB / T228.1-2021.

[0116] Electrochemical test: The samples were tested using the CHI600E electrochemical workstation produced by Shanghai Chenhua Company. The standard three-electrode system was used in the experiment, with the working electrode being the sample to be tested, the reference electrode being the calomel electrode, and the auxiliary electrode being the platinum electrode. A 3.5% NaCl aqueous solution was prepared as the corrosion medium (a 3.5% NaCl aqueous solution model), and the working electrode area was 3.14 cm 2 , the voltage test range is -2-0V, and the potential scanning rate is 3mV / s.

[0117] All test results were repeated 5 times and the average value was taken.

[0118] Table 1 Performance test results

[0119]

[0120] From the data in Table 1, we can see that the mechanical properties of the profiles in the embodiments of the present invention meet the requirements of more than 320MPa, the yield strength reaches more than 340MPa, and the elongation after fracture exceeds 10%, which meets the requirements of various components of new energy vehicles for mechanical properties. At the same time, the present invention has a higher corrosion potential and a lower corrosion current density. The higher the corrosion potential, the lower the tendency to corrosion; and the current density reflects the corrosion rate. The smaller the current density, the slower the corrosion rate, showing good corrosion resistance. However, the mechanical properties and corrosion resistance of Comparative Examples 1-6, which have changed the element composition, and Comparative Example 7, which has changed the composition of the surface treatment agent, have shown a certain degree of weakening. This is because the synergistic balance between La, Pr and Gd with different atomic radii and metamorphic abilities of Comparative Examples 1-6, which have changed the composition of rare earth elements, is broken, and the grain refinement and metamorphism are weakened, resulting in a decrease in overall mechanical properties and corrosion resistance.

[0121] Typical samples were selected, and the samples obtained in Example 1 and Comparative Examples 1-7 were used to observe the grain morphology under the polarized light mode of the ZEISSS microscope. Figure 1 As shown, the crystal grains of the sample of Example 1 of the present invention are small and uniform, while the crystal grains of the comparative example are relatively large. Comparative example 7 only involves the surface treatment part, and the crystal grain morphology is basically similar to that of Example 1.

[0122] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. An aluminum alloy profile for new energy vehicles, characterized in that: Calculated by mass percentage, it includes the following components: Fe0.14-0.19%, Si 0.58-0.66%, Mg0.6-1.3%, Cu0.25-0.35%, Mn0.07-0.15%, Cr0.14-0.22%, Zn0.01-0.05%, Ti0.03-0.15%, composite rare earth metal elements 0.6-0.9%, and the remainder is Al and impurities, wherein the total impurity content is not more than 0.25%.

2. The aluminum alloy profile for new energy vehicles according to claim 1, characterized in that: The composite rare earth metal elements are La, Pr and Gd, and the mass ratio of the three is 1:1:

1.

3. A method for preparing the aluminum alloy profile for new energy vehicles according to claim 1 or 2, characterized in that: The method comprises the following preparation steps: (1) Melting: Prepare the raw materials of various metal elements in proportion, melt the aluminum ingot, add other metal elements, heat and melt, and stir evenly to obtain an alloy melt; (2) Refining treatment: refining the alloy melt obtained in step (1) to complete degassing and impurity removal; (3) Casting: Casting the refined melt into an aluminum alloy ingot at a casting temperature of 700-750°C and a casting speed of 30-50 mm / min; (4) Homogenization treatment: placing the aluminum alloy ingot in a homogenization furnace for homogenization treatment at a temperature of 540-560° C. for a holding time of 5-10 h; (5) Cooling treatment: cooling the homogenized aluminum alloy ingot to 150-180° C. at a cooling rate of 100-120° C. / hour, and then cooling to room temperature by water mist; (6) Forming: The aluminum alloy ingot after cooling is sent into an extruder for extrusion molding, the extrusion temperature is 475-485°C, the extrusion rate is 10-12m / min, and the extrusion pressure is 120-150MPa; (7) Quenching and cooling: Quench the extruded material to room temperature, the quenching temperature is 455-465°C, keep it warm for 3-4 hours, and then water cool it to room temperature; (8) Artificial aging: The profiles after quenching and cooling are artificially aged at a temperature of 190-200°C for 5-7 hours, and finally cooled to room temperature; (9) Surface anti-corrosion treatment: Spray the surface treatment agent on the profile surface, cure at 170°C for 30 minutes, and then cool naturally.

4. The method for preparing the aluminum alloy profile for new energy vehicles according to claim 3, characterized in that: The smelting temperature of step (1) is 740-750° C. and the smelting time is 5-7 h.

5. The method for preparing the aluminum alloy profile for new energy vehicles according to claim 3, characterized in that: The refining method in step (2) is: using argon gas to blow a refining agent into the aluminum liquid formed by smelting to carry out furnace refining, the amount of the refining agent used is 1.5-2.5% of the weight of the alloy melt, and the furnace refining time is 17-20 minutes.

6. The method for preparing the aluminum alloy profile for new energy vehicles according to claim 3, characterized in that: Step (9) The surface treatment agent is a silica sol solution of a corrosion inhibitor, and the specific preparation method is as follows: 0.1mmol 2,5-furandicarboxylic acid and 0.1mmol cerium nitrate are added in sequence to 5ml of a mixed solvent, wherein the mixed solvent consists of N,N-dimethylacetamide, ethanol and deionized water in a volume ratio of 1:1:1; the mixed solution is ultrasonically treated for 15min and then transferred to a reactor, reacted at 95°C for 48h, cooled to room temperature and dried to obtain a corrosion inhibitor; nano-silica sol is taken, 1-3% of the corrosion inhibitor by mass of the nano-silica sol is added under ultrasound, after being fully dispersed, the pH of the system is adjusted to 4.5-5.5, and 10-15% of the mass of the nano-silica sol is added with methyltrimethoxysilane, and the mixture is mixed and reacted at room temperature for 8h to obtain a surface treatment agent.

7. The method for preparing the aluminum alloy profile for new energy vehicles according to claim 6, characterized in that: The nano silica sol has an average particle size of 30-50 nm and a mass concentration of 20-50%.

8. The method for preparing the aluminum alloy profile for new energy vehicles according to claim 3, characterized in that: The surface treatment agent spraying thickness is 1-3μm.

Citation Information

Patent Citations

  • Hydroxyl graphene modified coating sealant and preparation method thereof

    CN108129885A

  • Environment-friendly multi-metal water-based antirust agent and preparation method

    CN109763120A

  • High performance Al-Mg-Si aluminum alloy extrusion material and preparation method thereof

    CN110669964A

  • New energy automobile battery tray high-strength aluminum alloy sectional material and preparation method thereof

    CN111334690A

  • Improved high-heat-conductivity aluminum alloy material for automobile LED lamp support and preparation process thereof

    CN111690853A